2017
DOI: 10.3389/fams.2017.00024
|View full text |Cite
|
Sign up to set email alerts
|

Better Autologistic Regression

Abstract: Autologistic regression is an important probability model for dichotomous random variables observed along with covariate information. It has been used in various fields for analyzing binary data possessing spatial or network structure. The model can be viewed as an extension of the autologistic model (also known as the Ising model, quadratic exponential binary distribution, or Boltzmann machine) to include covariates. It can also be viewed as an extension of logistic regression to handle responses that are not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…However theoretical studies with this model by Wolters (2017) suggested better performance of a symmetrical coding rather than centering the model when associations (e.g. competition, spatial autocorrelations) were expected.…”
Section: Methodsmentioning
confidence: 93%
See 2 more Smart Citations
“…However theoretical studies with this model by Wolters (2017) suggested better performance of a symmetrical coding rather than centering the model when associations (e.g. competition, spatial autocorrelations) were expected.…”
Section: Methodsmentioning
confidence: 93%
“…Models with a centering term mostly used in ecology enabled modeling of the "large scale" response due to environmental predictors (centered auto-logistic models Hughes et al (2011)) which tried to detect auto-correlation in the residuals of a large scale response due to environmental drivers. However theoretical studies with this model by Wolters (2017) suggested better performance of a symmetrically coded model compare to a centered model when associations (e.g. competition, spatial autocorrelations) were expected.…”
Section: Hypothesismentioning
confidence: 89%
See 1 more Smart Citation
“…The link to drought occurrence at the previous time step is implicitly taken into account with previous precipitation or soil moisture anomalies. If previous system values are explicitly included as covariates to the model, one speaks of autologistic regression (Wolters, 2017).…”
Section: Time Series Modelingmentioning
confidence: 99%
“…The link to drought occurrence at the previous time step is implicitly taken into account with previous precipitation or soil moisture anomalies. If previous system values are explicitly included as covariates to the model, one speaks of auto-logistic regression (Wolters, 2017).…”
Section: Time Series Modelingmentioning
confidence: 99%